Recent Advances of Mn‐Rich LiFe1‐yMnyPO4 (0.5 ≤ y < 1.0) Cathode Materials for High Energy Density Lithium Ion Batteries. Issue 13 (20th February 2017) - Deng, Yuanfu; Yang, Chunxiang; Zou, Kaixiang; Qin, Xusong; Zhao, Zhenxia; Chen, Guohua
Abstract : LiMnPO4 (LMP) is one of the most potential candidates for high energy density (≈700 W h kg −1 ) lithium ion batteries (LIBs). However, the intrinsically low electronic conductivity and lithium ion diffusion coefficient of LMP result in its low performance. To overcome these challenges, it is an effective approach to prepare nanometer‐sized Fe‐doping LMP (LFMP) materials through optimization of the preparation routes. Moreover, surface coating can improve the ionic and electronic conductivity, and decrease the interfacial side reactions between the nanometer particles and electrolyte. Thus, a uniform surface coating will lead to a significant enhancement of the electrochemical performance of LFMP. Currently, considerable efforts have been devoted to improving the electrochemical performance of LiFe1‐ y Mn y PO4 (0.5 ≤ y < 1.0) and some important progresses have been achieved. Here, a general overview of the structural features, typical electrochemical behavior, delithiation/lithiation mechanisms, and thermodynamic properties of LiFe1‐ y Mn y PO4 ‐based materials is presented. The recent developments achieved in improvement of the electrochemical performances of LiFe1‐ y Mn y PO4 ‐based materials are summarized, including selecting the synthetic methods, nanostructuring, surface coating, optimizing Fe/Mn ratios and particle morphologies, cation/anion doping, and rational designing of LFMP‐based full cells. Finally, the critical issues at present and future development of LiFe1‐ y Mn y PO4 ‐based materials are discussed. Abstract : Mn‐rich LiFe1‐ y Mn y PO4 (0.5 ≤ y < 1.0) materials are among the most promising cathode materials for next generation of high‐energy‐density lithium ion batteries. The recent advances of the development of LiFe1‐ y Mn y PO4, especially on the studies of synthesis strategies, structural features, delithiation/lithiation mechanisms, thermodynamic properties, as well as some aspects for future exploration are outlined in this review.